Evaluación de Metales Traza en Agua y Sedimento Marino en la Ensenada Mackellar, Antártica (2018-2019) - Alfaro Jaucha, Jonathan Delio (2022)
There is concern about the anthropogenic impact on the Antarctic ecosystem, for this reason the Peruvian Marine Research Institute carried out the Twenty-Fifth and Sixth scientific expeditions of Peru to Antarctica. The investigations were carried out in the austral summer 2018-2019 aboard the BAP Carrasco from the Mackellar Cove located on King George Island, in which samples of water and marine sediment were taken at 11 sampling stations for the evaluation of trace metals (Cu, Zn, As and Pb) by inductively coupled plasma mass spectrometry (ICP-MS). It was observed that the highest concentration levels of Cu, As and Pb in the water matrix corresponded to the year 2019, compared to the year 2018. Also, these metals did not exceed the Environmental Quality Standards (EQS), for which it is considered that there is no risk of water contamination yet. However, there is a trend of increasing concentration of these metals each year. On the other hand, the concentrations of Cu and As in the sediment exceeded the EQS, so these metals could cause adverse effects on the marine ecosystem.